A tale of two syn-rifts: New age information and depositional environment interpretation for the North Falkland Basin syn-rift and implications for the rifting of Gondwana - Rory J. Sutton; Gayle E. Plenderleith; Thomas J.H. Dodd; Lorraine P. Field; Ian L. Millar; Dave J. McCarthy; Thomas A. Randles (Gondwana Research, 2026)

Past trajectory of a Northwest Europe socio-ecosystem at the land-sea interface: Case study of the northern watersheds of the Bay of Brest over the last 150 years - C. Valero; A. Penaud; M. Vidal; E. Goubert; P.A. Dessandier; S. Schmidt; E. Glémarec; P. Brigode; L. Bosseboeuf; Y.M. Paulet; J. Sutton; P. Ailliot; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The dolphin FRESH protocol: visual Freshwater-Related Evaluation of Skin Health in free-ranging bottlenose dolphins (Tursiops spp.) - Kristi L. Fazioli; Christina N. Toms; Ryan Takeshita; Alyssa Quackenbush; Denise Greig; Teresa Rowles; Lori Schwacke; Kathleen Colegrove; Ruth Y. Ewing; Deborah Fauquier; Denise Boyd; Aaron Bouwkamp; et al. (Frontiers in Marine Science, 2026)
Exposure to freshwater is a pressing health issue for coastal bottlenose dolphins ( Tursiops spp.). Environmental changes, including increased precipitation events and coastal infrastructure projects, are altering salinity within estuarine systems. Consequently, understanding effects of freshwater exposure on dolphins and developing tools to evaluate related health conditions is urgent. To address this need, a group of veterinarians, pathologists, epidemiologists, natural resource managers, and field biologists convened to create a protocol to visually assess freshwater-related skin lesions in free-ranging bottlenose dolphins. The Dolphin FRESH (Freshwater-Related Evaluation of Skin Health) Protocol guides users without medical backgrounds to screen and evaluate photographs by focusing on the visual identification of three primary indicators of freshwater skin disease: Overgrowth, Target-like Lesions, and Light Discoloration. By determining presence of the primary indicators and scoring associated characteristics, FRESH provides users with a relative assessment of the severity of these skin anomalies, and metrics to track progressive changes. The Scoring Rubric performed well during systematic testing, with evaluators correctly identifying freshwater cases through recognition of primary indicators and with no significant differences in total severity scores between field biologists and medical experts. FRESH is an important step in advancing knowledge on the effects of salinity fluctuations on dolphin health. When applied to photo datasets over time, this tool will enable researchers and managers to evaluate progression and regression of freshwater skin disease, occurrence and effects of multiple exposures, and the relationship between freshwater exposure skin indicators and health and survival outcomes.

Understanding the Impact of Psychosocial Barriers on Colorectal Cancer Knowledge in Emerging Adult Black Men - Chelsey McGill; Maria D. Thomson; Caroline Kuno; Emmanuel Taylor; Kimberly Lawrence; Alison J. Patev; Arnethea L. Sutton; Ruth Nyagaka; Oxana Palesh; Larry D. Keen (Journal of Cancer Education, 2026)
In the United States, Colorectal Cancer (CRC) is one of the most commonly diagnosed cancers and the third leading cause of death among non-Hispanic African American/Black (henceforth Black) men. Inadequate CRC knowledge leads to missing early warning signs, delaying prevention and increasing risk. Emerging adulthood (18–25) is a key period for building healthy behaviors and addressing barriers to CRC knowledge in addition to understanding attitudes and practices to CRC screening. Psychosocial barriers - including social support, medical mistrust, and perceived racial discrimination - contribute to the lack of CRC knowledge among older Black men, yet emerging adult Black men remain understudied. The present study examined psychosocial barriers to CRC knowledge among emerging adult Black men. Additionally, although not screening eligible, a secondary aim was to examine how these psychosocial barriers play a role CRC attitudes and preventive practices. One hundred sixty-eight men ( M age = 20.4, SD = 1.73) were recruited in Petersburg, Virginia. Participants completed a survey assessing social support, medical mistrust, and perceived racial discrimination, CRC knowledge, and CRC practice items. Data was analyzed using SPSS v.29. A hierarchical regression, controlling for age, public assistance status, and masculinity, examined social support, medical mistrust, and perceived racial discrimination. Contrary to hypothesis, higher medical mistrust predicted greater CRC knowledge, p = 0.003, while increased social support also predicted greater CRC knowledge, p < .001. Perceived racial discrimination did not significantly predict CRC knowledge. Logistic regressions showed that higher masculinity health problem minimization and perceived racial discrimination predicted significantly lower odds of considering early CRC screening. No variables significantly predicted early detection. Findings provide critical understanding of barriers and facilitators of CRC knowledge among emerging adult Black men. Addressing barriers during emerging adulthood may encourage healthier behaviors and foster motivation to seek CRC knowledge, ultimately supporting prevention in this high-risk population. Results are critical for informing culturally age-tailored prevention strategies.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Using pre-release efficacy as a candidate agent prioritisation tool for the weed Trichocereus spachianus (Caryophyllales: Cactaceae) - T. C. Griffith; M. B. Aguirre; G. F. Sutton; L. Chari; I. D. Paterson (BioControl, 2025)
Pre-release efficacy assessments (PREA) can be used to prioritise the most damaging candidate agents for further studies in biological control programmes against invasive alien plants. This study assessed the efficacy of various potential enemies of Trichocereus spachianus (Riccob.) (Caryophyllales: Cactaceae), an invasive cactus in South Africa, in order to prioritise the most damaging candidates for further studies, including host specificity testing. T. spachianus is considered indigenous in Argentina and Bolivia, but the original description was based on a cultivated plant, and it is either very rare or absent in its indigenous range, with no verified records of natural populations. This necessitates the use of new associations collected off close relatives of the target plant as potential biocontrol agents. We evaluated eight potential biocontrol agents by deriving host suitability indices (HSI) and performing efficacy trials. The HSI analysis demonstrated that only one out of the eight candidate agents, a cochineal insect Dactylopius confertus De Lotto (Hemiptera: Dactylopiidae), had high fitness (high survival, fecundity and complete development) on T. spachianus . This helped us eliminate ineffective agents early on in the programme. The cochineal insect was prioritised for efficacy trials, which demonstrated its high potential efficacy, killing approximately 89% of T. spachianus plants over 60 weeks. Taken together, our results indicated that D. confertus is a highly promising potential agent for the biocontrol of T. spachianus in South Africa. By prioritising candidate biocontrol agents based on efficacy prior to host specificity testing, we ensured that the highest priority candidate agent was identified for detailed and resource-intensive host specificity testing.

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

Effects of snake fungal disease (ophidiomycosis) on the skin microbiome across two major experimental scales - Alexander S. Romer; Matthew Grisnik; Jason W. Dallas; William Sutton; Christopher M. Murray; Rebecca H. Hardman; Tom Blanchard; Ryan J. Hanscom; Rulon W. Clark; Cody Godwin; N. Reed Alexander; Kylie C. Moe; et al. (Conservation Biology, 2025)
Emerging infectious diseases are increasingly recognized as a significant threat to global biodiversity conservation. Elucidating the relationship between pathogens and the host microbiome could lead to novel approaches for mitigating disease impacts. Pathogens can alter the host microbiome by inducing dysbiosis, an ecological state characterized by a reduction in bacterial alpha diversity, an increase in pathobionts, or a shift in beta diversity. We used the snake fungal disease (SFD; ophidiomycosis), system to examine how an emerging pathogen may induce dysbiosis across two experimental scales. We used quantitative polymerase chain reaction, bacterial amplicon sequencing, and a deep learning neural network to characterize the skin microbiome of free‐ranging snakes across a broad phylogenetic and spatial extent. Habitat suitability models were used to find variables associated with fungal presence on the landscape. We also conducted a laboratory study of northern watersnakes to examine temporal changes in the skin microbiome following inoculation with Ophidiomyces ophidiicola . Patterns characteristic of dysbiosis were found at both scales, as were nonlinear changes in alpha and alterations in beta diversity, although structural‐level and dispersion changes differed between field and laboratory contexts. The neural network was far more accurate (99.8% positive predictive value [PPV]) in predicting disease state than other analytic techniques (36.4% PPV). The genus Pseudomonas was characteristic of disease‐negative microbiomes, whereas, positive snakes were characterized by the pathobionts Chryseobacterium , Paracoccus , and Sphingobacterium . Geographic regions suitable for O. ophidiicola had high pathogen loads (>0.66 maximum sensitivity + specificity). We found that pathogen‐induced dysbiosis of the microbiome followed predictable trends, that disease state could be classified with neural network analyses, and that habitat suitability models predicted habitat for the SFD pathogen.

Predicting the invasiveness of alpine newts in the UK - Alexandra C. North; Luke J. Sutton; Jason L. Brown; Trenton W. J. Garner; Richard A. Billington; John W. Wilkinson; Manuela Truebano; Robert Puschendorf (Biological Invasions, 2025)
Predicting invasion risk to novel environments is essential for risk management and conservation decision making but the evolutionary lineage at which to make these predictions is often unclear. Here we predict the current suitability across the United Kingdom (UK) for the alpine newt Ichthyosaura alpestris , a species with a complex evolutionary history, a broad native range, a growing number of introduced populations and anecdotal reports of ecological consequences to native amphibian communities. We use species distribution and ecological niche modelling to predict environmental suitability of the alpine newt in the UK at both the species-level and lineage-level and to quantify evolutionary lineage niche overlap. We show good model transferability at the species-level and parts of the UK—especially central and eastern England and parts of central and northern Scotland—to be highly environmentally suitable for the alpine newt. Our findings provide evidence of environmental niche differences at the lineage-level, with the Greek lineage being distinct from most other lineages, but with low confidence in maxent predictions for the Greek, Balkan and Italian lineages due to high levels of extrapolation. In contrast, the niche of the UK records appear to share the same niche as the Central lineage. We find 66% of currently known alpine newt records to fall within areas predicted to be environmentally suitable at the species-level, providing a series of testable hypotheses to better understand the invasion ecology of this species in the UK.

Global screening of base excision repair in nucleosome core particles - Treshaun B. Sutton; Danielle L. Sawyer; Tasmin Naila; Joann B. Sweasy; Alan E. Tomkinson; Sarah Delaney (DNA Repair, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

Spatiotemporal analysis provides solutions to mitigate bycatch of southern Gulf of St. Lawrence Atlantic Cod in an expanding Redfish fishery - Jolene T. Sutton; Jenni L. McDermid; Lysandre Landry; François Turcotte (Fisheries Research, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Degradation of the 2014–2015 Holuhraun vent-proximal edifice in Iceland - S. S. Sutton; J. A. Richardson; P. L. Whelley; S. P. Scheidt; C. W. Hamilton (Bulletin of Volcanology, 2024)
The earliest stages of volcanic vent degradation are rarely measured, leaving a gap in the knowledge that informs landform degradation models of cinder cones and other monogenetic vent structures. We documented the initial degradation of a 500-m-long spatter rampart at the primary vent of the 2014–2015 Holuhraun eruption in northern Iceland with high-resolution topographic change maps derived from terrestrial laser scanning (TLS) and photogrammetric surveys using an unoccupied aircraft system (UAS). Topographic differencing shows a total negative volume change of 42,637 m 3 , and a total positive volume change (basal deposition) of 10,304 m 3 (primarily as deposition at the base of steeply sloping surfaces). Two distinct styles of volume changes were observed on the interior and exterior of the spatter rampart. Material on the interior of the vent was removed from oversteepened slopes by discrete rockfalls, while diffusive processes were qualitatively evident on the exterior slopes. We propose a novel conceptual landform evolution model for spatter ramparts that combines rockfall processes on the interior walls, diffusive gravitational sliding on the exterior slopes, and incorporates cooling contraction and compaction over the entire edifice to describe the observed modes of topographic change during the onset of degradation. Potential hazards at fresh spatter ramparts are rockfalls at high slope areas of the vent interior walls where contacts between spatter clasts are prone to weakening by fumarolic activity, weathering, and settling. To capture such hazards, our data suggest a cadence for monitoring changes yearly for the first few years post-eruption, and at longer intervals thereafter.

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

Drivers of CO2-carbonate system variability in the coastal ocean south of Honolulu, Hawai’i - Lucie A. C. M. Knor; Melissa Meléndez; Christopher L. Sabine; Adrienne J. Sutton (Frontiers in Marine Science, 2024)
This study examines carbonate chemistry variability from 2008 to 2021 in subtropical coastal waters adjacent to Honolulu, Hawai’i. We use surface seawater carbon dioxide partial pressure ( p CO 2 sw) measurements obtained every three hours from two buoys located along the south shore of O’ahu near anthropogenically impacted fringing reefs. The Ala Wai buoy was located 200 m offshore of a canal draining most of Honolulu, while the Kilo Nalu buoy was 1.3 miles (2 km) to the northwest, at a similar distance from shore with fewer terrestrial inputs. We compare p CO 2 sw variability from diurnal to interannual time scales. A trend analysis reveals a statistically significant increase in p CO 2 sw of +1.84 ± 0.27 µatm per year over the 11-year period. This rate is slightly lower than the average atmospheric growth rate observed during the same timeframe. In contrast to a nearby open-ocean site, the coastal sites experience amplified shorter-term variability, while seasonal to inter-annual variability is comparable to the open ocean. Ala Wai exhibits greater ranges than Kilo Nalu in all carbonate system variables due to its proximity to the Ala Wai Canal outflow. We examine the drivers that may explain both the similarities and contrasts in carbon dynamics observed between the two locations. Drivers of aragonite saturation state (Ω Ar ), an important variable for quantifying ocean acidification, are isolated from the in-situ time-series. Interannual salinity variations both due to freshwater pulses and large-scale regional salinity changes have a larger impact on Ω Ar than temperature changes, which mostly have an effect seasonally. A large biological contribution to Ω Ar is suspected, and further investigated using TA/DIC ratios normalized to median salinity and their slopes. Observed ratios at the south shore sites are evaluated relative to expected ratios derived from an open-ocean reference. Results suggest that dissolution and respiration are the primary biogeochemical processes occurring at these coastal sites. This highlights the significance of carbonate dissolution in anthropogenically impacted coastal waters, which is likely buffering acidification due to anthropogenic CO 2 and freshwater inputs at these sites.

Simulating productivity changes of epipelagic, mesopelagic, and bathypelagic taxa using a depth-resolved, end-to-end food web model for the oceanic Gulf of Mexico - Stacy Calhoun-Grosch; Jim J. Ruzicka; Kelly L. Robinson; Verena H. Wang; Tracey Sutton; Cameron Ainsworth; Frank Hernandez (Ecological Modelling, 2024)

Control of high-speed jumps in muscle and spring actuated systems: a comparative study of take-off energetics in bush-crickets (Mecopoda elongata) and locusts (Schistocerca gregaria) - Chloe K. Goode; Charlie Woodrow; Shannon L. Harrison; D. Charles Deeming; Gregory P. Sutton (Journal of Comparative Physiology B, 2023)
The Orthoptera are a diverse insect order well known for their locomotive capabilities. To jump, the bush-cricket uses a muscle actuated (MA) system in which leg extension is actuated by contraction of the femoral muscles of the hind legs. In comparison, the locust uses a latch mediated spring actuated (LaMSA) system, in which leg extension is actuated by the recoil of spring-like structure in the femur. The aim of this study was to describe the jumping kinematics of Mecopoda elongata (Tettigoniidae) and compare this to existing data in Schistocerca gregaria (Acrididae), to determine differences in control of rotation during take-off between similarly sized MA and LaMSA jumpers. 269 jumps from 67 individuals of M. elongata with masses from 0.014 g to 3.01 g were recorded with a high-speed camera setup. In M. elongata , linear velocity increased with mass 0.18 and the angular velocity (pitch) decreased with mass −0.13 . In S. gregaria , linear velocity is constant and angular velocity decreases with mass −0.24 . Despite these differences in velocity scaling, the ratio of translational kinetic energy to rotational kinetic energy was similar for both species. On average, the energy distribution of M. elongata was distributed 98.8% to translational kinetic energy and 1.2% to rotational kinetic energy, whilst in S. gregaria it is 98.7% and 1.3%, respectively. This energy distribution was independent of size for both species. Despite having two different jump actuation mechanisms, the ratio of translational and rotational kinetic energy formed during take-off is fixed across these distantly related orthopterans.

Standardizing gross descriptions of skin lesions in common bottlenose dolphins (Tursiops truncatus) stranded in Southwest Florida, 2015–2019 - Ruth Y. Ewing; Meghan N. Sutton; Hada M. Herring; Molly R. Schubert; Denise M. Boyd; Jill L. Richardson; David S. Rotstein (Frontiers in Marine Science, 2023)
As the first line of defense, the integumentary system is critical in comprehensively evaluating dolphin morbidity during stranding response. Most published studies on skin lesions in bottlenose dolphins (Tursiops truncatus) lack standardized gross descriptions and methodologies for evaluating lesions. The primary objective of this study was to evaluate the effectiveness of an assessment matrix designed to consistently describe skin lesions based on a set of standardized gross description characteristics. The matrix was implemented by reviewing necropsy reports, histopathology reports, and photographs collected from bottlenose dolphins stranded in Southwest Florida from 2015 through 2019. Of the 32 dolphins that met the inclusion criteria, 19 presented with skin lesions and five reviewers described each of the 46 lesions according to a novel, standardized assessment matrix. The most common descriptor selected, in each of the respective matrix categories, were, by anatomic location, head; distribution, multifocal to coalescing; quantity, moderate (10–30); size, <2 cm; shape, punctate; margin, rounded; color modifier, hyperpigmentation; texture, smooth; and texture modifier, flat. These prevalent descriptors coincided with the frequent occurrence of histologically described hydropic degeneration (n=7, 15.2%) and were confirmed poxviral lesions in 6.52% (n=3). Identifying lesion patterns using standardized descriptors capitalizes on the unique pathogen tissue tropism and the implementation of certain disease mechanisms in the integumentary system. Therefore, it can facilitate differential disease diagnoses and guide ancillary diagnostics testing. The use of standardized descriptors will aid in etiologic identification and monitoring of skin lesions and associated diseases, advancing our understanding of dolphin morbidity and mortality.

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

GeoSoilEnviroCARS (Sector 13) at the Advanced Photon Source: a comprehensive synchrotron radiation facility for Earth science research at ambient and extreme conditions - S. R. Sutton; M. L. Rivers; S. Chariton; P. J. Eng; A. Lanzirotti; M. Newville; T. Officer; V. B. Prakapenka; Y. J. Ryu; J. E. Stubbs; S. Tkachev; Y. Wang; et al. (Physics and Chemistry of Minerals, 2022)

Environmental factors associated with Baylisascaris procyonis infection from a population of raccoons in Toronto, Ontario, Canada - Shannon K. French; David L. Pearl; William B. Sutton; Andrew S. Peregrine; Claire M. Jardine (Urban Ecosystems, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Systems analysis of miRNA biomarkers to inform drug safety - Amy L. Schofield; Joseph P. Brown; Jack Brown; Ania Wilczynska; Catherine Bell; Warren E. Glaab; Matthias Hackl; Lawrence Howell; Stephen Lee; James W. Dear; Mika Remes; Paul Reeves; et al. (Archives of Toxicology, 2021)
microRNAs (miRNAs or miRs) are short non-coding RNA molecules which have been shown to be dysregulated and released into the extracellular milieu as a result of many drug and non-drug-induced pathologies in different organ systems. Consequently, circulating miRs have been proposed as useful biomarkers of many disease states, including drug-induced tissue injury. miRs have shown potential to support or even replace the existing traditional biomarkers of drug-induced toxicity in terms of sensitivity and specificity, and there is some evidence for their improved diagnostic and prognostic value. However, several pre-analytical and analytical challenges, mainly associated with assay standardization, require solutions before circulating miRs can be successfully translated into the clinic. This review will consider the value and potential for the use of circulating miRs in drug-safety assessment and describe a systems approach to the analysis of the miRNAome in the discovery setting, as well as highlighting standardization issues that at this stage prevent their clinical use as biomarkers. Highlighting these challenges will hopefully drive future research into finding appropriate solutions, and eventually circulating miRs may be translated to the clinic where their undoubted biomarker potential can be used to benefit patients in rapid, easy to use, point-of-care test systems.

Attitudes and Perceptions Towards Radiation Therapy in Breast Cancer Patients: The Role of a Multidisciplinary Care Team - Yasamin Sharifzadeh; Alexander N. Slade; Elisabeth Weiss; Arnethea L. Sutton; Vanessa B. Sheppard (Journal of Cancer Education, 2021)

Reaching Rural Residents to Identify Colorectal Cancer Education and Intervention Targets - Arnethea L. Sutton; Michael A. Preston; Maria Thomson; Charlotte Litzenberg; Trina F. Taylor; Eva Polly Cole; Vanessa B. Sheppard (Journal of Cancer Education, 2021)

Synergistic effects of harvest and climate drive synchronous somatic growth within key New Zealand fisheries - John R. Morrongiello; Peter L. Horn; Caoimhghin Ó Maolagáin; Philip J. H. Sutton (Global Change Biology, 2021)
Fisheries harvest has pervasive impacts on wild fish populations, including the truncation of size and age structures, altered population dynamics and density, and modified habitat and assemblage composition. Understanding the degree to which harvest‐induced impacts increase the sensitivity of individuals, populations and ultimately species to environmental change is essential to ensuring sustainable fisheries management in a rapidly changing world. Here we generated multiple long‐term (44–62 years), annually resolved, somatic growth chronologies of four commercially important fishes from New Zealand's coastal and shelf waters. We used these novel data to investigate how regional‐ and basin‐scale environmental variability, in concert with fishing activity, affected individual somatic growth rates and the magnitude of spatial synchrony among stocks. Changes in somatic growth can affect individual fitness and a range of population and fishery metrics such as recruitment success, maturation schedules and stock biomass. Across all species, individual growth benefited from a fishing‐induced release of density controls. For nearshore snapper and tarakihi, regional‐scale wind and temperature also additively affected growth, indicating that future climate change‐induced warming and potentially strengthened winds will initially promote the productivity of more poleward populations. Fishing increased the sensitivity of deep‐water hoki and ling growth to the Interdecadal Pacific Oscillation (IPO). A forecast shift to a positive IPO phase, in concert with current harvest strategies, will likely promote individual hoki and ling growth. At the species level, historical fishing practices and IPO synergized to strengthen spatial synchrony in average growth between stocks separated by 400–600 nm of ocean. Increased spatial synchrony can, however, increase the vulnerability of stocks to deleterious stochastic events. Together, our individual‐ and species‐level results show how fishing and environmental factors can conflate to initially promote individual growth but then possibly heighten the sensitivity of stocks to environmental change.

Men’s experiences of radiotherapy treatment for localized prostate cancer and its long-term treatment side effects: a longitudinal qualitative study - E. Sutton; J. A. Lane; M. Davis; E. I. Walsh; D. E. Neal; F. C. Hamdy; M. Mason; J. Staffurth; R. M. Martin; C. Metcalfe; T. J. Peters; J. L. Donovan; et al. (Cancer Causes & Control, 2021)
Purpose To investigate men’s experiences of receiving external-beam radiotherapy (EBRT) with neoadjuvant Androgen Deprivation Therapy (ADT) for localized prostate cancer (LPCa) in the ProtecT trial. Methods A longitudinal qualitative interview study was embedded in the ProtecT RCT. Sixteen men with clinically LPCa who underwent EBRT in ProtecT were purposively sampled to include a range of socio-demographic and clinical characteristics. They participated in serial in-depth qualitative interviews for up to 8 years post-treatment, exploring experiences of treatment and its side effects over time. Results Men experienced bowel, sexual, and urinary side effects, mostly in the short term but some persisted and were bothersome. Most men downplayed the impacts, voicing expectations of age-related decline, and normalizing these changes. There was some reticence to seek help, with men prioritizing their relationships and overall health and well-being over returning to pretreatment levels of function. Some unmet needs with regard to information about treatment schedules and side effects were reported, particularly among men with continuing functional symptoms. Conclusions These findings reinforce the importance of providing universal clear, concise, and timely information and supportive resources in the short term, and more targeted and detailed information and care in the longer term to maintain and improve treatment experiences for men undergoing EBRT.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Medical Mistrust in Black Breast Cancer Patients: Acknowledging the Roles of the Trustor and the Trustee - Arnethea L. Sutton; Jun He; Megan C. Edmonds; Vanessa B. Sheppard (Journal of Cancer Education, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Hawaii Coastal Seawater CO2 Network: A Statistical Evaluation of a Decade of Observations on Tropical Coral Reefs - Gerianne J. Terlouw; Lucie A. C. M. Knor; Eric Heinen De Carlo; Patrick S. Drupp; Fred T. Mackenzie; Yuan Hui Li; Adrienne J. Sutton; Albert J. Plueddemann; Christopher L. Sabine (Frontiers in Marine Science, 2019)

Tropical Pacific Observing System - Neville Smith; William S. Kessler; Sophie Cravatte; Janet Sprintall; Susan Wijffels; Meghan F. Cronin; Adrienne Sutton; Yolande L. Serra; Boris Dewitte; Peter G. Strutton; Katherine Hill; Alex Sen Gupta; et al. (Frontiers in Marine Science, 2019)

The Second Warning to Humanity – Providing a Context for Wetland Management and Policy - C. M. Finlayson; Gillian T. Davies; William R. Moomaw; G. L. Chmura; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2019)

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Restructuring of a mutualism following introduction of Australian fig trees and pollinating wasps to Europe and the USA - E. J. Morgan; T. L. Sutton; C. T. Darwell; J. M. Cook (Biological Invasions, 2018)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Environmental evidence for a pygmy blue whale aggregation area in the Subtropical Convergence Zone south of Australia - Maria I. Garcia‐Rojas; K. Curt S. Jenner; Peter C. Gill; Micheline‐Nicole M. Jenner; Alicia L. Sutton; Robert D. McCauley (Marine Mammal Science, 2018)
The importance of the Subtropical Convergence Zone south of Australia as a feeding area to the pygmy blue whale of the eastern Indian Ocean was investigated to better understand migration patterns and habitat use. A combination of satellite tagging studies during 2003–2005 and acoustic and visual surveys during the austral summer of 2013 confirmed the presence of pygmy blue whales in the Subtropical Convergence Zone and provided evidence for feeding throughout the region. Of the 67 pygmy blue whales acoustically detected, many were localized in proximity to sea surface temperature fronts and high chlorophyll concentrations, which could be a behavioral strategy to attract conspecifics to good feeding sites. Aggregations of up to four pygmy blue whales, along with decreased call rates during the day, may suggest feeding despite no direct observations of pygmy blue whales consuming euphausiids. The oceanographic features present throughout the Subtropical Convergence Zone continue to create an environment productive enough to support the world's largest living mammals during their migratory foraging movements between the Southern Ocean and Indonesia.

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Energy expenditure of rugby players during a 14-day in-season period, measured using doubly labelled water - Deborah R. Smith; R. F. G. J. King; L. C. Duckworth; L. Sutton; T. Preston; J. P. O’Hara; B. Jones (European Journal of Applied Physiology, 2018)

Decadal predictions with the HiGEM high resolution global coupled climate model: description and basic evaluation - L. C. Shaffrey; D. Hodson; J. Robson; D. P. Stevens; E. Hawkins; I. Polo; I. Stevens; R. T. Sutton; G. Lister; A. Iwi; D. Smith; A. Stephens (Climate Dynamics, 2017)

Ranavirus could facilitate local extinction of rare amphibian species - Julia E. Earl; Jordan C. Chaney; William B. Sutton; Carson E. Lillard; Andrew J. Kouba; Cecilia Langhorne; Jessi Krebs; Rebecca P. Wilkes; Rachel D. Hill; Debra L. Miller; Matthew J. Gray (Oecologia, 2016)

Influence of the Leeuwin Current on the epipelagic euphausiid assemblages of the south-east Indian Ocean - Alicia L. Sutton; Lynnath E. Beckley (Hydrobiologia, 2016)

Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Travis A. Courtney; Andreas J. Andersson; Nicholas R. Bates; Andrew Collins; Tyler Cyronak; Samantha J. de Putron; Bradley D. Eyre; Rebecca Garley; Eric J. Hochberg; Rodney Johnson; Sylvia Musielewicz; Tim J. Noyes; et al. (Frontiers in Marine Science, 2016)

One step ahead: a parasitoid disperses farther and forms a wider geographic population than its fig wasp host - Timothy L. Sutton; Markus Riegler; James M. Cook (Molecular Ecology, 2016)
The structure of populations across landscapes influences the dynamics of their interactions with other species. Understanding the geographic structure of populations can thus shed light on the potential for interacting species to co‐evolve. Host–parasitoid interactions are widespread in nature and also represent a significant force in the evolution of plant–insect interactions. However, there have been few comparisons of population structure between an insect host and its parasitoid. We used microsatellite markers to analyse the population genetic structure of Pleistodontes imperialis sp. 1, a fig‐pollinating wasp of Port Jackson fig ( Ficus rubiginosa ), and its main parasitoid, Sycoscapter sp. A, in eastern Australia. Besides exploring this host–parasitoid system, our study also constitutes, to our knowledge, the first study of population structure in a nonpollinating fig wasp species. We collected matched samples of pollinators and parasitoids at several sites in two regions separated by up to 2000 km. We found that pollinators occupying the two regions represent distinct populations, but, in contrast, parasitoids formed a single population across the wide geographic range sampled. We observed genetic isolation by distance for each species, but found consistently lower F ST and R ST values between sites for parasitoids compared with pollinators. Previous studies have indicated that pollinators of monoecious figs can disperse over very long distances, and we provide the first genetic evidence that their parasitoids may disperse as far, if not farther. The contrasting geographic population structures of host and parasitoid highlight the potential for geographic mosaics in this important symbiotic system.

An assessment of age and growth of violet cod (Antimora rostrata) in the Ross Sea, Antarctica - Peter L. Horn; Colin P. Sutton (Polar Biology, 2015)

A Direct Pre-screen for Marine Bacteria Producing Compounds Inhibiting Quorum Sensing Reveals Diverse Planktonic Bacteria that are Bioactive - Jamie S. Linthorne; Barbara J. Chang; Gavin R. Flematti; Emilio L. Ghisalberti; David C. Sutton (Marine Biotechnology, 2015)

Simulation of CO2 and Attribution Analysis at Six European Peatland Sites Using the ECOSSE Model - M. Abdalla; A. Hastings; M. J. Bell; J. U. Smith; M. Richards; M. B. Nilsson; M. Peichl; M. O. Löfvenius; M. Lund; C. Helfter; E. Nemitz; M. A. Sutton; et al. (Water, Air, & Soil Pollution, 2014)

Vaccine Delivery to the Oral Cavity Using Coated Microneedles Induces Systemic and Mucosal Immunity - Yunzhe Ma; Wenqian Tao; Shelly J. Krebs; William F. Sutton; Nancy L. Haigwood; Harvinder S. Gill (Pharmaceutical Research, 2014)

Potential Applicability of Persuasive Communication to Light-Glow Reduction Efforts: A Case Study of Marine Turtle Conservation - Ruth L. Kamrowski; Stephen G. Sutton; Renae C. Tobin; Mark Hamann (Environmental Management, 2014)

Arabidopsis thaliana PDX1.2 is critical for embryo development and heat shock tolerance - Jan Erik Leuendorf; Sutton L. Mooney; Liyuan Chen; Hanjo A. Hellmann (Planta, 2014)

Characterization of MHC class II B polymorphism in bottlenecked New Zealand saddlebacks reveals low levels of genetic diversity - Jolene T. Sutton; Bruce C. Robertson; Catherine E. Grueber; Jo-Ann L. Stanton; Ian G. Jamieson (Immunogenetics, 2013)

Anaerobic Metabolism in Tidal Freshwater Wetlands: III. Temperature Regulation of Iron Cycling - Allyson L. Bullock; Ariana E. Sutton-Grier; J. Patrick Megonigal (Estuaries and Coasts, 2013)

Anaerobic Metabolism in Tidal Freshwater Wetlands: I. Plant Removal Effects on Iron Reduction and Methanogenesis - Jason K. Keller; Ariana E. Sutton-Grier; Allyson L. Bullock; J. Patrick Megonigal (Estuaries and Coasts, 2013)

Anaerobic Metabolism in Tidal Freshwater Wetlands: II. Effects of Plant Removal on Archaeal Microbial Communities - David Emerson; Wendy Bellows; Jason K. Keller; Craig L. Moyer; Ariana Sutton-Grier; J. Patrick Megonigal (Estuaries and Coasts, 2013)

Illustrating the critical role of human dimensions research for understanding and managing recreational fisheries within a social‐ecological system framework - L. M. Hunt; S. G. Sutton; R. Arlinghaus (Fisheries Management and Ecology, 2013)
Effective management of recreational fishing requires understanding fishers and their actions. These actions constitute critical links between social and ecological systems that result in outcomes that feedback and influence recreational fishers' actions and the management of these actions. Although much research exists on recreational fishers and their actions, this research is often disconnected from management issues. One way to help to overcome this disconnect is to illustrate how past research on the social component of recreational fishing fits within an emerging coupled social‐ecological system ( SES ) framework. Herein, a conceptual SES is first developed with specific attention to recreational fisheries. This SES is then used to illustrate the importance of considering human dimensions research for articulating, studying and ultimately managing key outcomes of recreational fisheries (e.g. fish population conservation, fisher well‐being) using the example of harvest regulations and a brief review of past interdisciplinary research on recreational fishing. The article ends by identifying key research needs including understanding: how factors such as management rules affect the diversity of actions by recreational fishers; how governance and management approaches adapt to changing social and resource conditions; and how recreational fishers learn and share information.

A verification framework for interannual-to-decadal predictions experiments - L. Goddard; A. Kumar; A. Solomon; D. Smith; G. Boer; P. Gonzalez; V. Kharin; W. Merryfield; C. Deser; S. J. Mason; B. P. Kirtman; R. Msadek; et al. (Climate Dynamics, 2013)

The impact of resolution on the adjustment and decadal variability of the Atlantic meridional overturning circulation in a coupled climate model - Daniel L. R. Hodson; Rowan T. Sutton (Climate Dynamics, 2012)

RANTES/CCL5-induced pro-angiogenic effects depend on CCR1, CCR5 and glycosaminoglycans - N. Suffee; H. Hlawaty; A. Meddahi-Pelle; L. Maillard; L. Louedec; O. Haddad; L. Martin; C. Laguillier; B. Richard; O. Oudar; D. Letourneur; N. Charnaux; et al. (Angiogenesis, 2012)

Internal waves downstream of Norfolk Ridge, western Pacific, and their biophysical implications - Craig L. Stevens; Philip J. H. Sutton; Cliff S. Law N (Limnology and Oceanography, 2012)
An 11‐d quasi‐Lagrangian surface layer experiment to the east of Norfolk Island tracked a 140‐m‐deep drifting vertical array (DVA) of instruments, including conductivity sensors, thermistors, and current meters. These are the first in situ data from the area to measure large‐amplitude internal waves. The observations show isotherm peak‐to‐peak excursions reaching 50 m and were dominated by the semidiurnal forcing frequency. The DVA exhibited horizontal loops at the semidiurnal tidal frequency as it tracked water at depths of 80‐140 m to within 10% of total horizontal displacement. The large vertical isotherm excursions generated substantial vertical shear. Temperature microstructure estimates of the vertical diffusivity of scalar properties at 70‐m depth, around the center of the thermocline, were on the order of 10 −4 m 2 s −1 and around an order of magnitude larger at shallower depths. When combined with nitrate data, this implies vertical fluxes of nitrate in the pycnocline of ∼ 1 mmol m −2 d −1 . The internal waves also potentially cause an interaction between the variability in tidal forcing and the diurnal radiation cycle that influences chlorophyll in the deep chlorophyll maximum. The average effect of the internal wave was to increase the light level for a particular isotherm over the static case. The internal wave‐induced velocities were strong enough to dominate phytoplankton rise speeds and so potentially played a role in the formation and persistence of an observed Trichodesmium bloom.

Comparison of microbial communities in pilot-scale bioreactors treating Bayer liquor organic wastes - Naomi J. McSweeney; Jason J. Plumb; Amanda L. Tilbury; Hugh J. Nyeboer; Matt E. Sumich; Anthony J. McKinnon; Peter D. Franzmann; David C. Sutton; Anna H. Kaksonen (Biodegradation, 2011)

Chemical and antimicrobial treatments change the viscoelastic properties of bacterial biofilms - Warren L. Jones; Michael P. Sutton; Ladean McKittrick; Philip S. Stewart (Biofouling, 2011)

Characterizing relationships between population density and nighttime imagery for Denver, Colorado: issues of scale and representation - Sharolyn J. Anderson; Benjamin T. Tuttle; Rebecca L. Powell; Paul C. Sutton (International Journal of Remote Sensing, 2010)

Does brachial artery flow-mediated dilation scale to anthropometric characteristics? - N. D. Hopkins; D. J. Green; T. M. Tinken; L. Sutton; N. McWhannell; N. T. Cable; G. Stratton; K. George (European Journal of Applied Physiology, 2010)

Climate impacts of recent multidecadal changes in Atlantic Ocean Sea Surface Temperature: a multimodel comparison - Daniel L. R. Hodson; Rowan T. Sutton; Christophe Cassou; Noel Keenlyside; Yuko Okumura; Tianjun Zhou (Climate Dynamics, 2010)

Characterisation of bacteria in ascites—reporting the potential of culture-independent, molecular analysis - G. B. Rogers; L. E. Russell; P. G. Preston; P. Marsh; J. E. Collins; J. Saunders; J. Sutton; D. Fine; K. D. Bruce; M. Wright (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Development of a low-cost system for measuring conditional time-averaged gradients of SO2 and NH3 - D. Famulari; D. Fowler; E. Nemitz; K. J. Hargreaves; R. L. Storeton-West; G. Rutherford; Y. S. Tang; M. A. Sutton; K. J. Weston (Environmental Monitoring and Assessment, 2010)

A review of climate risk information for adaptation and development planning - R. L. Wilby; J. Troni; Y. Biot; L. Tedd; B. C. Hewitson; D. M. Smith; R. T. Sutton (International Journal of Climatology, 2009)
Although the use of climate scenarios for impact assessment has grown steadily since the 1990s, uptake of such information for adaptation is lagging by nearly a decade in terms of scientific output. Nonetheless, integration of climate risk information in development planning is now a priority for donor agencies because of the need to prepare for climate change impacts across different sectors and countries. This urgency stems from concerns that progress made against Millennium Development Goals (MDGs) could be threatened by anthropogenic climate change beyond 2015. Up to this time the human signal, though detectable and growing, will be a relatively small component of climate variability and change. This implies the need for a twin‐track approach: on the one hand, vulnerability assessments of social and economic strategies for coping with present climate extremes and variability, and, on the other hand, development of climate forecast tools and scenarios to evaluate sector‐specific, incremental changes in risk over the next few decades. This review starts by describing the climate outlook for the next couple of decades and the implications for adaptation assessments. We then review ways in which climate risk information is already being used in adaptation assessments and evaluate the strengths and weaknesses of three groups of techniques. Next we identify knowledge gaps and opportunities for improving the production and uptake of climate risk information for the 2020s. We assert that climate change scenarios can meet some, but not all, of the needs of adaptation planning. Even then, the choice of scenario technique must be matched to the intended application, taking into account local constraints of time, resources, human capacity and supporting infrastructure. We also show that much greater attention should be given to improving and critiquing models used for climate impact assessment, as standard practice. Finally, we highlight the over‐arching need for the scientific community to provide more information and guidance on adapting to the risks of climate variability and change over nearer time horizons (i.e. the 2020s). Although the focus of the review is on information provision and uptake in developing regions, it is clear that many developed countries are facing the same challenges. Copyright © 2009 Royal Meteorological Society

Exploring multi-model atmospheric GCM ensembles with ANOVA - D. L. R. Hodson; R. T. Sutton (Climate Dynamics, 2008)

Re-engineering the target specificity of clostridial neurotoxins - a route to novel therapeutics - Keith A. Foster; Emily J. Adams; Lyndsey Durose; Caroline J. Cruttwell; Elizabeth Marks; Clifford C. Shone; John A. Chaddock; Clare L. Cox; Charlotte Heaton; J. Mark Sutton; Jonathan Wayne; Frances C. G. Alexander; et al. (Neurotoxicity Research, 2006)

Accurately measuring volcanic plume velocity with multiple UV spectrometers - Glyn Williams-Jones; Keith A. Horton; Tamar Elias; Harold Garbeil; Peter J. Mouginis-Mark; A. Jeff Sutton; Andrew J. L. Harris (Bulletin of Volcanology, 2006)

Allele-specific methylation of a functional CTCF binding site upstream of MEG3 in the human imprinted domain of 14q32 - Alberto L. Rosa; Yuan-Qing Wu; Bernard Kwabi-Addo; Karen J. Coveler; V. Reid Sutton; Lisa G. Shaffer (Chromosome Research, 2005)

Temporal changes in the relationship between condition indices and proximate composition of juvenile Coregonus artedi - K. L. Pangle; T. M. Sutton (Journal of Fish Biology, 2005)
The Fulton‐condition factor ( K ) and per cent whole‐body water content were examined to determine whether these indices can estimate the proximate composition of juvenile lake herring Coregonus artedi exposed to a simulated Lake Superior winter over a 225 day laboratory experiment. The K was positively correlated to whole‐body crude lipid, crude protein, and gross energy content and negatively correlated to whole‐body water content for each sampling period of the experiment (days 75, 150 and 225). In contrast, there was only a weak positive correlation between K and whole‐body ash content. While per cent water content was negatively correlated with crude lipid, crude protein and gross energy content for each of the three sampling periods, the correlation between this predictor and ash content was only weakly negative. The indices can be used to accurately estimate temporal changes in proximate composition of juvenile lake herring during winter periods.

An intercomparison between the surface heat flux feedback in five coupled models, COADS and the NCEP reanalysis - C. Frankignoul; M. Botzet; A. F. Carril; E. Kestenare; H. Drange; A. Pardaens; L. Terray; R. Sutton (Climate Dynamics, 2004)

Species Richness and Invasion Vectors: Sampling Techniques and Biases - S. Gollasch; H. Rosenthal; H. Botnen; M. Crncevic; M. Gilbert; J. Hamer; N. Hülsmann; C. Mauro; L. McCann; D. Minchin; B. Öztürk; M. Robertson; et al. (Biological Invasions, 2003)

What motivates interest in attending a familial cancer genetics clinic? - L. Fraser; S. Bramald; C. Chapman; C. Chu; V. Cornelius; F. Douglas; A. Lucassen; A. Nehammer; S. Sutton; M. Trivella; S. Hodgson (Familial Cancer, 2003)

Genetic Relationship of Tumor-Associated Piscine Retroviruses - Sandra L. Quackenbush; Joel Rovnak; Rufina N. Casey; Thomas A. Paul; Paul R. Bowser; Claudia Sutton; James W. Casey (Marine Biotechnology, 2001)

Alice grows up: canopy science in transition from Wonderland to Reality - Stephen L. Sutton (Plant Ecology, 2001)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Establishing white spruce in the Boreal White and Black Spruce Zone - L. Bedford; R.F. Sutton; L. Stordeur; M. Grismer (New Forests, 2000)

Effects of Selective Logging on the Butterflies of a Bornean Rainforest - S. J. Willott; D. C. Lim; S. G. Compton; S. L. Sutton (Conservation Biology, 2000)
Selective logging has been the main cause of disturbance to tropical forests in Southeast Asia, so the extent to which biodiversity is maintained in selectively logged forest is of prime conservation importance. We compared the butterfly assemblages of Bornean primary rainforest to those of rainforest selectively logged 6 years previously. We sampled by means of replicated transects stratified into riverine and ridge forests and we included roads in the logged forest. There was a three‐fold variation in species richness and abundance over the 8‐month sampling period. More species and individuals were observed in the logged forest, although between‐replicate variability was high. Rarefied species richness was positively correlated with canopy openness within the range of disturbance levels encountered at our forest sites. Within families, there was no significant difference in the number of species between primary and logged forest. There was a significant difference in the relative abundance of species, but this was due largely to the abundance of one or two species. Community ordination separated the sites along a gradient of disturbance and revealed strong differences between riverine and ridge‐forest butterfly assemblages in primary forest that were obscured in logged forest. There was no evidence that logging has resulted in a change in the composition of the butterfly assemblages from species with a local distribution to more widespread species. We conclude that at a logged forest site in close proximity to primary forest, low intensities of logging do not necessarily reduce the species richness or abundance of butterflies, although assemblage composition is changed.

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Relationships of aphid and mite infestations to control ofBotrytis cinerea byClonostachys rosea in rose(Rosa hybrida) leaves - M. A. B. Morandi; J. C. Sutton; L. A. Maffia (Phytoparasitica, 2000)

Glucose, and not sucrose, is transported from wheat to wheat powdery mildew - P. N. Sutton; M. J. Henry; J. L. Hall (Planta, 1999)

Operation Everest II: An indication of deterministic chaos in human heart rate variability at simulated extreme altitude - Yoshiharu Yamamoto; Richard L. Hughson; John R. Sutton; Charles S. Houston; Allen Cymerman; Ernest L. Fallen; Marked V. Kamath (Biological Cybernetics, 1993)

Variable group size can further reduce animal usage in acute toxicity tests - T. J. Sutton; L. M. Reilly (Archives of Toxicology, 1991)

The acute and chronic toxicity of ten chlorinated organic compounds to the American flagfish (Jordanella floridae) - A. D. Smith; A. Bharath; C. Mallard; D. Orr; K. Smith; J. A. Sutton; J. Vukmanich; L. S. McCarty; G. W. Ozburn (Archives of Environmental Contamination and Toxicology, 1991)